(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article aims to present the circus manifestations in Basic Education in Brazil. The study adopted the exploratory research of multiple bibliographic and multimedia sources, analysed through Interpretive Analysis. The results shows much circus manifestations occur in Basic Education, carried out by artists, teacher s and art-educators. The results pointed out that professional artistic presentations; courses, workshops, conferences and others; Tours-Lessons; extracurricular projects and complementary activities do not constitute school knowledge because they are not articulate with the curriculum. However, pluri, inter and transdisciplinary projects, the curricular disciplines of the Circus, and teaching as a theme, content and didactic resource in the subjects make the Circus a school knowledge subject to the devices of the school institution and organization. Thus, this study seeks to value the diversity of actions, projects, activities, and people who seek to bring the Circus, its art and wisdom closer to Basic Education.